Cholinergic modulation of Up–Down states in the mouse medial entorhinal cortex in vitro. (17th December 2020) - Hay, Y. Audrey; Jarzebowski, Przemyslaw; Zhang, Yu; Digby, Richard; Brendel, Viktoria; Paulsen, Ole; Magloire, Vincent
Abstract: Cholinergic tone is high during wake and rapid eye movement sleep and lower during slow wave sleep (SWS). Nevertheless, the low tone of acetylcholine during SWS modulates sharp wave ripple incidence in the hippocampus and slow wave activity in the neocortex. Linking the hippocampus and neocortex, the medial entorhinal cortex (mEC) regulates the coupling between these structures during SWS, alternating between silent Down states and active Up states, which outlast neocortical ones. Here, we investigated how low physiological concentrations of acetylcholine (ACh; 100–500 nM) modulate Up and Down states in a mEC slice preparation. We find that ACh has a dual effect on mEC activity: it prolongs apparent Up state duration as recorded in individual cells and decreases the total synaptic charge transfer, without affecting the duration of detectable synaptic activity. The overall outcome of ACh application is excitatory and we show that ACh increases Up state incidence via muscarinic receptor activation. The mean firing rate of principal neurons increased in around half of the cells while the other half showed a decrease in firing rate. Using two‐photon calcium imaging of population activity, we found that population‐wide network events are more frequent and rhythmic during ACh and confirmed that ACh modulates cell participation in these network events, consistent with a role for cholinergic modulation in regulating information flow between the hippocampus and neocortex during SWS. Abstract : Slow wave sleep (SWS) is characterised by a low tone of acetylcholine (ACh), which modulates sharp wave ripple incidence in the hippocampus and neocortical slow wave activity. The medial entorhinal cortex (mEC) couples hippocampal and neocortical activity during SWS and is highly sensitive to ACh. Using electrophysiology and Ca 2+ imaging, we show that a sleep‐like tone of ACh modulates mEC Up states via muscarinic receptors and reorganises how neuronal circuits are recruited during Up states.